OBTENCIÓN DE LA MATRIZ DE VARIANZAS Y COVARIANZAS A TRAVÉS DE LOS PRODUCTOS KRONECKER PARA MODELOS BALANCEADOS - Moya Moya, Luz Marina; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2003)
We present a method for constructing variance and covariance matrices for balanced design using the Kronecker product. The method can be applied to fixed, random, or mixed models with any number of factors. The covariance matrices are constructed under the usual infinite and finite model assumptions.